Astro royale. Volume 2 - Wakui, Ken (VIZ Media, LLC, 2025)
Hibaru Yotsurugi, the only biological heir to the Yotsurugi yakuza family, is caught in a power struggle with his adopted siblings over who will be the next boss. But when a meteorite crashes into Tokyo and people begin manifesting mysterious powers called Astros in the aftermath, their gang war becomes superpowered! After recruiting Kuran, the head of the Ikebukuro branch, Hibaru and Terasu learn that the Hawk faction has been stealing Astro links, the source of people's Astro powers, and that their older brother Torazo is one of the victims! It's up to Hibaru's gang to help restore Torazo's Astro!